Gazaltı kaynak metali özellikleri - Çalış, İrfan (My University, 1999)
In thıs thesis bead shape of gas shielded electric arc welding steel weld metal was examined theoretically and experimentally. The effects of welding parameters on bead shape were explained. In experimental studies GTAW, MIG, and MAG welding processes were applied. Bead on plate, partial and full penetration butt joints were prepared. Mild steel sheet and plate samples were used in the experiments. The following results were derived from the experiments: 1- Weld metal size is directly proportional to welding energy input. 2- Weld current - welding travel speed maps for full penetration of butt welds were drawn for GTAW, MIG and MAG welding proccesses. 3- In GTAW welds maximum penetration is obtained at 10o pulling angle. 4- In MAG welds maximum penetration is optained at 20o pulling angle. 5- In MIG welds maximum penetration is optained at 30o pulling angle. 6- In MIG and MAG welding processes, welding current and welding voltage must be controlled together to obtain maximum penetration. 7- In GTAW welding penetration is indirectly proportional to electrode head angle.
Keywords: KAYNAK